Effects of topical otic preparations on hearing in chronic otitis media - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1997)
Most of the topical otic preparations have been shown to cause ototoxicity. In this study ciprofloxacin hydrochloride, a relatively new topical agent, and gentamicin sulfate were studied in two groups of 20 patients with chronic otitis media, Patients were randomly selected to receive either ciprofloxacin (200 mu g/ml) or gentamicin sulfate (5 mg/ml) locally, five drops three times a day for 10 days. Clinical response was seen in 20 of 20 patients in the ciprofloxacin group compared with 6 of 20 patients in the gentamicin group, Audiometric evaluation revealed no significant ototoxic effect in either group, In fact, hearing thresholds were slightly better than pretreatment levels in both groups.
Keywords: CIPROFLOXACIN; GENTAMICIN; EAR